Visual field analysis in patients with Parkinson's disease - MİDİ, İPEK; ŞAHİN, ÖZLEM (ELSEVIER SCI LTD, 2008)
Background: To evaluate visual field changes in patients with Parkinson's disease. Methods: Standard automated perimetry of 14 patients (28 eyes) with Parkinson's disease (PD) were compared with controls. PD patients with Unified Parkinson's Disease Rating Scale (UPDRS) score below 25 were included in the study. Results: Visual field indices including mean deviation (-4.69 +/- 2.72 vs. -1.71 +/- 1.30, p = 0.0008), pattern standard deviation (3.94 +/- 1.94 vs. 2.30 +/- 0.41, p = 0.001), and corrected pattern standard deviation (3.23 +/- 2.18 vs. 1.20 +/- 0.91, p = 0.003), were significantly worse in patients with PD when compared with the control group. Bilateral glaucoma-like visual field defects were evident in six patients. Conclusion: Parkinson's patients had worse visual field indices suggesting a common insult in the etiopathogenesis of nerve fiber layer damages observed in glaucoma and PD. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Parkinson's disease; neurodegenerative diseases; glaucoma-like visual field defects; EVOKED-POTENTIALS; PATTERN ELECTRORETINOGRAM; EXPERIMENTAL GLAUCOMA; AUTOMATED PERIMETRY; GANGLION-CELLS; BLUE-YELLOW; APOPTOSIS; DOPAMINE; NEURONS; DEATH